Capturing the cultural boundary among the members' interactions in a multinational workgroup: An evidence from System for the Multiple Level Observation of Groups analysis - Ming-Yen Lee; Quynh-Trang Nguyen (Cogent Business & Management, 2019)
In order to capture the cultural boundary among international group members under the globalization context, this study conducted SYMLOG (A System for the Multiple Level Observation of Groups) approach through a case study on an international marine transport company. With questionnaire surveys, on-site observation, and individual and group interview, we adopted the field diagrams, interaction forms and thematic analysis to examine differences among members' interactions, which resulted from a cultural boundary. The findings clearly explained the cultural impacts on individual behaviors and indicated that cultural schema will lead group members with similar cultural backgrounds to create a boundary toward members from different backgrounds. It also provided valuable insights and management guidance for leaders of multicultural teams to handle differences and conflicts due to cultural forces.
Keywords: 650; Globalization; Personnel Selection; Assessment; Human Resource Management; Business